Vitamin B-12 is neuroprotective in experimental pneumococcal meningitis through modulation of hippocampal DNA methylation - Queiroz, Karina Barbosa de; Cavalcante-Silva, Vanessa; Lopes, Flavia Lombardi [UNESP]; Rocha, Gifone Aguiar; D'Almeida, Vania; Coimbra, Roney Santos (Bmc, 2020)
Background Bacterial meningitis (BM) causes apoptotic damage to the hippocampus and homocysteine (Hcy) accumulation to neurotoxic levels in the cerebrospinal fluid of children. The Hcy pathway controls bioavailability of methyl, and its homeostasis can be modulated by vitamin B-12, a cofactor of the methionine synthase enzyme. Herein, the neuroprotective potential and the underlying mode of action of vitamin B-12 adjuvant therapy were assessed in an infant rat model of BM. Methods Eleven-day old rats were intracysternally infected with Streptococcus pneumoniae serotype 3, or saline, treated with B-12 or placebo, and, 24 h after infection, their hippocampi were analyzed for apoptosis in the dentate gyrus, sulfur amino acids content, global DNA methylation, transcription, and proximal promoter methylation of candidate genes. Differences between groups were compared using 2-way ANOVA followed by Bonferroni post hoc test. Correlations were tested with Spearman's test. Results B-12 attenuated BM-induced hippocampal apoptosis in a Hcy-dependent manner (r = 0.80, P < 0.05). BM caused global DNA hypomethylation; however, B-12 restored this parameter. Accordingly, B-12 increased the methylation capacity of hippocampal cells from infected animals, as inferred from the ratio S-adenosylmethionine (SAM):S-adenosylhomocysteine (SAH) in infected animals. BM upregulated selected pro-inflammatory genes, and this effect was counteracted by B-12, which also increased methylation of CpGs at the promoter of Ccl3 of infected animals. Conclusion Hcy is likely to play a central role in hippocampal damage in the infant rat model of BM, and B-12 shows an anti-inflammatory and neuroprotective action through methyl-dependent epigenetic mechanisms.
Keywords: Meningitis; Neuroprotection; Vitamin B-12; Epigenetics; Homocysteine; DNA methylation